Pengaruh Inventory Turnover dan Working Capital Turnover Dengan Current Ratio Sebagai Mediasi terhadap Harga Saham Pada Sub Sektor Industri Kabel di Bursa Efek Indonesia - Ali Akbar (Universitas Batanghari Jambi, 2023)
The purpose of this research is to know and analyze the influence of inventory turnover and working capital turnover mediating the current ratio on stock price in the cable industry sub-sector on the Indonesia stock exchange. This research used secondary data from annual financial statements and closing stock prices. The sample in the research is the cable industry sub-sector on the Indonesia Stock Exchange for the 2016-2021 period. The sampling method uses purposive sampling. Data analysis in this research used path analysis with SPSS software. The results of the research inform: ''1) indirectly inventory turnover and working capital turnover mediating the current ratio have insignificant effect on the stock price. 2) Inventory turnover and working capital turnover simultaneously have significant effect on current ratio. 3) Inventory turnover has negative and significant effect on current ratio. 4) Working capital turnover has positive and significant effect on current ratio. 5) Inventory turnover and working capital turnover simultaneously have significant effect on stock prices. 6) Inventory turnover has negative and significant effect on stock prices. 7) Working capital turnover has negative and insignificant effect on stock prices. 8) Current ratio has positive and insignificant effect on stock prices”.